Comparative Effectiveness of Anti-Inflammatory Drug Treatments in Coronary Heart Disease Patients: A Systematic Review and Network Meta-Analysis - Ivan Wudexi; Elica Shokri; Mohamed Abo-Aly; Kazuhiro Shindo; Ahmed Abdel-Latif (Mediators of Inflammation, 2021)
Introduction and Hypothesis. The role of inflammation is widely recognized in the pathogenesis of coronary artery disease. Research on animal models had shown the potential benefits of targeting specific inflammatory pathways. However, studies on human subjects are limited with small number of patients and no head-to-head comparisons. Methods. We conducted a network meta-analysis of randomized controlled trials that studied the effects of anti-inflammatory medications on cardiovascular outcomes of coronary artery disease patients. We searched the electronic database until March 2020 for relevant studies. Results. Nineteen trials examining the efficacy of eight anti-inflammatory medications (pexelizumab, anakinra, colchicine, darapladib, varespladib, canakinumab, inclacumab, and losmapimod) were selected for analysis. Overall, there is no statistically significant difference in all-cause mortality, cardiovascular mortality, revascularization, and major cardio and cerebrovascular events (MACCE) with the use of anti-inflammatory drugs. However, we found the use of colchicine significantly reduces the odds of developing stroke by approximately 75% (OR 0.26, CI 0.10-0.63). Colchicine use was also associated with a lower risk of revascularization and MACCE compared to the other agents. Our subgroup analyses comparing the timing of medication initiation (within 7 days vs. >7 days) and clinical presentation (ACS vs. non-ACS) revealed a significant reduction in the risk of recurrent MI in the group that received medication after seven days (OR 0.92, CI 0.86-0.99) and the non-ACS group (OR 0.88, CI 0.80-0.98). Conclusion. Although many anti-inflammatory medications have failed to reduce adverse cardiovascular outcomes in the CAD population, selected medications show promise among subgroups of patients without ACS or after the first week following an acute ischemic event. Future studies examining the proper timing and targetable anti-inflammatory pathways are warranted.